Propuesta para la creación una tienda virtual de ropa street style (2024)
The creation of a virtual clothing store is a strategic proposal that seeks to take advantage of the opportunities of electronic commerce and satisfy the demands of fashion consumers. In this proposal, research has been carried out on the online fashion market. It will be designed considering an intuitive and attractive interface, along with an effective digital marketing strategy. This is justified by the need to overcome geographical limitations, offer a greater variety of products, establish close relationships with customers and reduce operating costs. By implementing this virtual store, it is expected to establish a solid presence in the online fashion market and provide a personalized and satisfying shopping experience